The frequency of clinical manifestations of hypophosphatemic rickets in patients with therapeutic strategies - Leila Kanafi Vahed; Afshin Arianpur; Mohammad Esmaeili (Clinics and Practice, 2018)
The aim of this study was to evaluate the frequency of clinical manifestations of various types of rickets in patients could be effective in therapeutic strategies. A total of eleven child patients (7 females and 4 males) were included in the present study. The patients were admitted to the hospital with hypophosphatemic rickets. In our study, the age at the time of diagnosis ranged from 1 to15 years. Mean age of first presentations at final diagnosis was determined to be 5.5 an 2 years, respectively. Five patients out of 11 patients had showed significant history of vitamin D3 resistance. Family history of similar skeletal problems was reported to be positive in six patients. Furthermore, there were seven relative marriages in parents. Mean value of Gomez index has been revealed as 64%. Mean serum phosphate level was detected as 2.9 mg/dL, that this level in males (2.2 mg/dL) was significantly less than females (3.4 mg/dL) (P=0.5). Mean serum alkaline phosphatase activity was reached 913 IU/L. Alkaline phosphatase activity in women (1075 IU/L) was significantly lower than that of men (750 IU/L), (P=0.5). Definitive treatment with oral phosphate and vitamin D3 can prevent complications of the disease and the side effects of unconventional treatments.